“Did you try virtual sex?”: Sexological discourse and digital culture in times of COVID-19 - Martynowskyj, Estefania (2022)
In this paper, it is exploring the discourses on sexuality that, in the context of the covid-19 pandemic, are reproduce and circulate on Instagram accounts of six Argentine sexologists who do sex education and publicize their professional work through these social media. From digital ethnographic explorations we analyze how these professionals construct a way of narrating the knowledge of sexology on the internet; deploy pedagogical activities that position them as new references in the field of national sexology and configure a network of “instagramers” dedicated to sex education.